Impact of embolization on stereotactic radiosurgery outcomes for intracranial arteriovenous malformations Spetzler-Martin grades III–V: a systematic review and meta-analysis - Lauren, Christopher; Niryana, I Wayan; Mahadewa, Tjokorda Gde Bagus (Frontiers in Surgery, 2025)
IntroductionIntracranial arteriovenous malformations (AVMs) classified as Spetzler-Martin (SM) grades III-V present significant therapeutic challenges due to their complex angioarchitecture and high risk of morbidity. Stereotactic radiosurgery (SRS) is a minimally invasive modality for nidus obliteration, often combined with embolization to reduce nidus size and address high-risk vascular features. However, the impact of pre-SRS embolization on obliteration rates, post-SRS hemorrhage, and mortality remains controversial. This systematic review and meta-analysis aim to evaluate the effects of embolization on SRS outcomes in high-grade AVMs.MethodsFollowing PRISMA guidelines, a comprehensive search of PubMed, ScienceDirect, Cochrane, and Google Scholar was conducted. Studies comparing SRS alone versus SRS with embolization in SM grade III-V AVMs were included. Primary outcomes were obliteration rates, post-SRS hemorrhage, and mortality. Data extraction and quality assessment were performed using the Newcastle-Ottawa Scale, and pooled analysis was conducted using Review Manager (RevMan) software.ResultsOut of 4,186 identified studies, five high-quality cohort studies met inclusion criteria. Pooled analysis showed that SRS alone resulted in higher obliteration rates than SRS with embolization (OR: 2.06, 95% CI: 0.92–4.65; p=0.08), though not statistically significant. Post-SRS hemorrhage rates were comparable (OR: 3.07, 95% CI: 0.72–13.08; p = 0.13), and mortality rates showed no significant difference (OR: 0.21, 95% CI: 0.01–4.62; p = 0.32).DiscussionAlthough embolization aids in nidus volume reduction, it may hinder radiosurgical efficacy by altering nidus architecture and introducing shielding effects. SRS alone demonstrated superior obliteration rates with fewer technical concerns. Individualized treatment planning remains essential, balancing embolization benefits against its potential drawbacks. Future studies should explore advancements in embolic agents and imaging techniques to optimize multimodal strategies for high-grade AVMs.